Nitric oxide synthase inhibition in rats: Melatonin reduces blood pressure and ischemia/reperfusion-induced infarct size - Deniz, Esra; Sahna, Engin; Aksulu, Hakki Engin (Taylor & Francis Ltd, 2006)
Reduction in the synthesis or bioavailability of nitric oxide plays a significant role in the development of myocardial infarction and hypertension. Numerous studies suggest that melatonin reduces blood pressure (BP) and ischemia/reperfusion (I/R) injury in rats. The effects of melatonin on the BP and I/R-induced cardiac infarct size in L-NAME-induced hypertensive rats remains unknown. This study was designed to investigate the effects of melatonin on BP and the I/R-induced infarct size in chronic nitric oxide synthase inhibited rats by L-NAME. Rats received L-NAME for 15 days to produce hypertension and melatonin the last 5 days before I/R studies. To produce cardiac damage, the left coronary artery was occluded for 30 min, followed by 120 min reperfusion. L-NAME led to a significant increase in BP. Melatonin administration (10 mg/kg) to L-NAME treated rats significantly reduced BP and infarct size. Also, melatonin attenuated the mortality resulting from I/R, but this was not statistically significant. Melatonin administration would seem important to reduce BP and infarct size resulting from I/R in L-NAME-induced hypertensive rats.
Keywords: Myocardial Ischemia-Reperfusion; Essential-Hypertension; Oxidative Stress; Injury; Reduction; Disease; Roles; Heart